Nutritional Screening and Anthropometry in Patients Admitted From the Emergency Department - Speranza, Enza; Santarpia, Lidia; Marra, Maurizio; Di Vincenzo, Olivia; Naccarato, Marianna; De Caprio, Carmela; Morlino, Delia; D'Onofrio, Gaetano; Contaldo, Franco; Pasanisi, Fabrizio (Frontiers in Nutrition, 2022)
Background: Due to the high prevalence of malnutrition among hospitalized patients, screening and assessment of nutritional status should be routinely performed upon hospital admission. The main objective of this observational study was to evaluate the prevalence of and the risk for malnutrition, as identified by using three nutritional screening tests, and to observe whether some anthropometric and functional parameters used for nutritional evaluation were related to these test scores. Methods This single-centre observational study included 207 patients admitted from the emergency department for hospitalization in either the internal medicine or surgery units of our institution from September 2017 to December 2018. The prevalence of malnutrition among this patient sample was evaluated by using the Nutritional Risk Screening (NRS-2002), the Subjective Global Assessment (SGA) and the Global Leadership Initiative on Malnutrition (GLIM) criteria. Body mass index (BMI), bioimpedance analysis (BIA), handgrip strength (HGS) and calf circumference (CC) assessments were also performed. Results: According to the NRS-2002, 93% of the patients were at no risk or at low nutritional risk (NRS score < 3), and 7% were at a high nutritional risk (NRS score ≥ 3). On the other hand, according to the SGA, 46.3% of the patients were well nourished (SGA-a), 49.8% were moderately malnourished (SGA-b), and 3.9% were severely malnourished (SGA-c). Finally, according to the GLIM criteria, 18% patients were malnourished. Body weight, body mass index (BMI), phase angle (PhA), CC and HGS were significantly lower in the patients with NRS scores ≥ 3, SGA-c and in patients with stage 1 and stage 2 malnutrition, according to the GLIM criteria. Conclusion: The NRS-2002, the SGA and the GLIM criteria appear to be valuable tools for the screening and assessment of nutritional status. In particular, the lowest NRS-2002, SGA and GLIM scores were associated with the lowest PhA and CC. Nevertheless, a weekly re-evaluation of patients with better screening and assessment scores is recommended to facilitate early detection of changes in nutritional status.